Canada, Then Scatology, Then the Novels of David Williams - Kramer, Reinhold (Studies in Canadian Literature, 1990)
Marshall McLuhan has offered the Deconstructionist argument that Canada is a "hidden ground" existing as a cipher between two logo-centres. Canada is a gap in the text, showing up geographically, but washed clean of history. Yet, Linda Hutcheon has suggested that the historiographic impulse to address other national histories can be seen as Canada's entry into the world community. Recourse to other histories of production inevitably leads one to the metaphor of scatology, for production invariably leads to waste, and a culture can thus be known by its waste. The historicizing writer, then, can often destroy gaps by using scatology as a sign of presence. In David Williams' first two books, The Burning Wood and The River Horsemen, scatology traces the marginalizing of the Native that haunts Canadian history; in Eye of the Father, Williams, by using scatology, presents a careful response to the notion of the Canadian self as a depleted and innocent sign.